Prevalence and factors associated with lung function abnormalities among rice millworkers in Sokoto state, Northwest Nigeria - Ayotunde Sherif Azees; Mansur Oche; Abdulfattah Isa; Abiola Temitayo-Oboh; Jessica Ango; Abdullahi Shehu; Nurudeen Adana (Occupational Health and Safety Society of Nepal, 2022)
Introduction: Northwest Nigeria has witnessed an increase in rice milling activities due to the ban on rice importation. The majority of workers in the industry, as it is in many informal sectors workers are disproportionately affected by hazards in the workplace due to poor usage of protective devices. Inhalation of dust over a long period results in lung function abnormalities. The study assessed the prevalence and factors associated with lung function abnormalities among rice mill workers in Sokoto state, Northwest Nigeria. Methods: The study was conducted using a cross-sectional design. Data were collected between June 2019 and July 2019 using an interviewer-administered questionnaire and a lung function examination was conducted using a calibrated Contec SP10 digital spirometer following standardized procedures. Data were analyzed using IBM SPSS version 23 and presented in tables and charts. Results: About a third of 119 (30.2%) of the respondents had abnormalities on spirometry, and there was a statistically significant reduction in the mean FVC (3.63 ± 0.39) and FEV1 (3.01 ± 0.36). Being at least 30 years of age (aOR=3.3), working more than 8 hours a day (aOR=2.4), and having at least a symptom of respiratory morbidity (aOR=10.1) were the factors found to be significantly associated with lung function abnormalities. Conclusion: This study showed that the prevalence of lung function abnormality among rice mill workers in Sokoto state is relatively high and age, number of hours worked per day and having at least a symptom of respiratory morbidity were the factors associated with lung function abnormalities.